PENGEMBANGAN ALAT PRAKTIKUM KEPOLARAN DI SMA MUHAMMADIYAH 1 PONTIANAK - Surya Wahyudi; Raudhatul Fadhilah; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2019)
Methods applied in schools have not been able to make students understand the sub-material of polar and nonpolar covalent compounds. One of the success factors of the practicum method is the use of the right practicum tools. Therefore, it is necessary to develop practical tools to make it easier for students to understand the concepts of polar and nonpolar covalent compounds. This study aims to produce a polarity and practicum tool on sub-material polar and nonpolar covalent compounds that are valid, practical, and effective. Validity is measured from the validator's assessment on material aspects and media using a validation sheet. Practicality is measured using teacher and student response questionnaires. Effectiveness is measured by the results of students' Pretest and Postest. This type of research is the development of the ADDIE Research and Development (R & D) model (Analysis, Design, Development, Implementation, and Evaluation). The results of the analysis show that the polarity practicum tool developed from the material and media aspects was stated to be very valid with an average validity value of 0.83 and 0.89, respectively. The practicality test results obtained very practical criteria with a practicality value of 96.64%. The aspect of effectiveness using the N-Gain value in the field trial results obtained N-Gain values of 0.72 with very high criteria. Thus, the polarity practicum tool developed is suitable for use as a sub-material learning media for polar and nonpolar covalent compounds.